Knee replacement. Issue 10158 (3rd November 2018) - Price, Andrew J; Alvand, Abtin; Troelsen, Anders; Katz, Jeffrey N; Hooper, Gary; Gray, Alastair; Carr, Andrew; Beard, David
Summary: Knee replacement surgery is one of the most commonly done and cost-effective musculoskeletal surgical procedures. The numbers of cases done continue to grow worldwide, with substantial variation in utilisation rates across regions and countries. The main indication for surgery remains painful knee osteoarthritis with reduced function and quality of life. The threshold for intervention is not well defined, and is influenced by many factors including patient and surgeon preference. Most patients have a very good clinical outcome after knee replacement, but multiple studies have reported that 20% or more of patients do not. So despite excellent long-term survivorship, more work is required to enhance this procedure and development is rightly focused on increasing the proportion of patients who have successful pain relief after surgery. Changing implant design has historically been a target for improving outcome, but there is greater recognition that improvements can be achieved by better implantation methods, avoiding complications, and improving perioperative care for patients, such as enhanced recovery programmes. New technologies are likely to advance future knee replacement care further, but their introduction must be regulated and monitored with greater rigour to ensure patient safety.